Performance of the CR-MAC with Channel Fading and Capture Effect under Practical Traffic Scenarios for VANETs - Karabulut, Muhammet Ali; Shah, A. F. M. Shahen; Ilhan, Haci (IEEE, 2019)
In this paper, performance of cooperative relaying medium access control (CR-MAC) protocol [1] is investigated for vehicular ad hoc networks (VANETs) with channel fading and capture effect under practical traffic scenarios. Though the present analysis based on idle channel condition, in reality, the performance depends on channel fading and capture effect. To understand actual performance the real traffic scenario is needed. An analytical model based on Markov chain model is presented. The expressions of frame capture probability, probability of successful transmission, probability of unsuccessful transmission and throughput are obtained. Realistic traffic model is generated in SUMO. Simulation results are presented.
Keywords: Capture effect; channel fading; CR-MAC; realistic traffic model; VANETs; PROTOCOL; Computer Science; Engineering; Telecommunications